Equality issues for the new millennium - Shah, Sneh (Routledge revivals., 2018)
First published in 2000, this volume is taking stock of equality issues in higher education as we move into the new millennium. It is clear that many positive developments in the 1970s and 1980s have been lost. However, the way forward is not just to reinstate these developments. This book focuses on a number of challenges, including bringing equality issues from the periphery to the centre of education, seeking an overarching framework such as human rights to ensure that equality is interpreted in a more comprehensive and systematic way, including every individual in the deliberations about equality, and accepting that an acknowledgement of the 'needs' of specific groups of students has to be paralleled with educating everyone about their responsibilities in relation to the causes and consequences of inequality. Fifteen educationalists, from a number of higher education institutions, have analyzed their particular area of work in equality, providing the clear message that in the new millennium equality must become truly embedded in real education.